Poly(lactic acid)/graphite nanoplatelet nanocomposite filaments for ligament scaffolds - Silva, Magda (2021)
The anterior cruciate ligament (ACL) is one of the most prone to injury in the human body. Due to its insufficient vascularization and low regenerative capacity, surgery is often required when it is ruptured. Most of the current tissue engineering (TE) strategies are based on scaffolds produced with fibers due to the natural ligamentâ s fibrous structure. In the present work, composite filaments based on poly(L-lactic acid) (PLA) reinforced with graphite nanoplatelets (PLA+EG) as received, chemically functionalized (PLA+f-EG), or functionalized and decorated with silver nanoparticles [PLA+((f-EG)+Ag)] were produced by melt mixing, ensuring good filler dispersion. These filaments were produced with diameters of 0.25 mm and 1.75 mm for textile-engineered and 3D-printed ligament scaffolds, respectively. The resulting composite filaments are thermally stable, and the incorporation of graphite increases the stiffness of the composites and decreases the electrical resistivity, as compared to PLA. None of the filaments suffered significant degradation after 27 days. The composite filaments were processed into 3D scaffolds with finely controlled dimensions and porosity by textile-engineered and additive fabrication techniques, demonstrating their potential for ligament TE applications.